(untitled) (Journal of Plant Disease Sciences, 2023)
Maize is one of the world’s most significant cereal crops, ranking third only to wheat and rice. Many funguses are seed-borne and cause significant devastation diseases. Fungi have a significant impact on grain and seed storage quality. In current study, eight seed samples were collected from eight districts of Marathwada in order to determine the seed mycoflora of maize. Dry seed examination, towel paper, standard blotter, and agar plate method were used to examine maize seed samplesfor seed myco-flora. Visual observations of maize seeds revealed that deformed seeds, discoloured seeds, damaged seeds, impurities (inert materials), and healthy seeds were present in seed samples. Visual observations of maize seeds revealed that deformed seeds, discoloured seeds, damaged seeds, impurities (inert matters) and healthy seeds in seed samples. Maximum (88%) of healthy seeds was recorded in sample collected from Parbhani district followed by 86% collected from Hingoli district. Fusarium moniliformae, Aspergillus niger, Aspergillus flavus, Rhizoctonia bataticola, Curvularia lunata, Rhizopus stolonifer, Fusarium oxysporum, Alternaria alternata were identified as seed-borne myco-flora in three detection methods with maize seeds and among all seed borne fungi Fusarium moniliformae was observed as pre dominant fungi inmaize.